Constitutively Active 5-HT Receptors: An Explanation of How 5-HT Antagonists Inhibit Gut Motility in Species Where 5-HT is Not an Enteric Neurotransmitter? - Spencer, Nick J. (Frontiers in Cellular Neuroscience, 2015)
Antagonists of 5-Hydroxytryptamine (5-HT) receptors are well known to inhibit gastrointestinal (GI)-motility and transit in a variety of mammals, including humans. Originally, these observations had been interpreted by many investigators (including us) as evidence that endogenous 5-HT plays a major role in GI motility. This seemed a logical assumption. However, the story changed dramatically after recent studies revealed that 5-HT antagonists still blocked major GI motility patterns (peristalsis and colonic migrating motor complexes) in segments of intestine depleted of all 5-HT. Then, these results were further supported by Dr. Gershons’ laboratory, which showed that genetic deletion of all genes that synthesizes 5-HT had minor, or no inhibitory effects on GI transit in vivo. If 5-HT was essential for GI motility patterns and transit, then one would expect major disruptions in motility and transit when 5-HT synthesis was genetically ablated. This does not occur. The inhibitory effects of 5-HT antagonists on GI motility clearly occur independently of any 5-HT in the gut. Evidence now suggests that 5-HT antagonists act on 5-HT receptors in the gut which are constitutively active, and don’t require 5-HT for their activation. This would explain a long-standing mystery of how 5-HT antagonists inhibit gut motility in species like mice, rats and humans where 5-HT is not an enteric neurotransmitter. Studies are now increasingly demonstrating that the presence of a neurochemical in enteric neurons does not mean they function as neurotransmitters. Caution should be exercised when interpreting any inhibitory effects of 5-HT antagonists on GI motility.